Pengaruh Waktu Dan Suhu Ekstraksi Dan Karakteristik Pektin Dari Kulit Buah Coklat (Theobroma Cacao) - Hadi, Teuku Luthfi; Sami, Muhammad (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
The chocolate fruit (Theobroma Cacao) that is considered to have economic value is the seed, while the skin is underutilized. Brown peel is a processing waste from chocolate beans. Pectin comes from the Greek word pectos which means to freeze or clump. Vangueli was the first to discover the existence of a substance that could form gel derived from fruits and succeeded in isolating it as a substance that could be dissolved in water. In this study, the extraction of brown skin pectin was carried out by extraction method using Microwave Assisted Extraction (MAE). This study aims to determine the number of yields produced, the influence of time and temperature on yields, moisture content, methoxyl content, equivalent weight and functional groups. The raw material for the source of pectin is the peel of the chocolate fruit by the solvent extraction method. The fixed variable used was the skin of a chocolate fruit weighing 20 grams, as a marinating agent used an HCl solution with a concentration of 0.05 N. In this study, two independent variables were used, namely the extraction temperature of 65°C and the extraction time of 55 minutes. From the results of the study, the best results were obtained in 35 minutes at a temperature of 85°C of 12.72% pectin yield with a moisture content of 9%. High methoxyl levels were obtained at a temperature of 65°C and a time of 45 minutes was 10.08%, an equivalent weight of 625 mg, this shows that pectin has data according to SNI.